Analysis of Increasing Efficiency of Gas Turbines by Using Absorption Refrigerator (AR) - Nassipkul Dyussembekova; Andrey Kibarin; Dias Umyshev; Saulesh Minazhova (Proceedings of the International Conference on Applied Innovations in IT, 2019)
The paper presents an analysis of the gas turbine power plant’s (GTPP) operation. It is shown that in summer the efficiency of GTPP is significantly reduced due to the high air temperature on the inlet of the compressor. In the summer, the efficiency and, accordingly, the production of electric energy is reduced due to high temperatures of the ambient air. This article presents an analysis of the possibility of increasing the efficiency of the gas turbine engine. The analysis shows that the use of absorption refrigerator (AR) in hot periods of the year, in which the outside air temperature exceeds 20 degrees is the optimal solution. The analysis showed that the use of AR allows to increase efficiency and specific heat consumption by 3 %, capacity by 14 % (5,5 % annually) MW and reduce fuel consumption by 2,5-3 %. The experience of modernization of gas turbine unit (GTU) is available, for the installation of AR it will be required about 2500 million tenge (6000 US dollars). Taking into account the economic effect of 740 million tenge, a simple payback period for the introduction of air cooling systems at GTPP will be about 4 years.